A Life Course Approach to Understanding Neighbourhood Effects - Elise de Vuijst; Maarten van Ham; Reinout Kleinhans (Institute for the Study of Labor (IZA), 2016)
Many theories on so-called neighbourhood effects – effects of the residential context on individual outcomes such as employment, education, and health – implicitly, or explicitly suggest lagged effects, duration effects, or for example, intergenerational effects of neighbourhoods. However, these temporal dimensions of neighbourhood effects receive only limited attention in the empirical literature, largely because of a lack of suitable data. The increasing availability of geo-coded, longitudinal, individual-level data now leads to more research which takes these temporal dimensions and time effects into account. This paper argues that it is time for an overarching framework to better understand the temporal dimension of neighbourhood effects. We propose a conceptual model that uses the life course approach as a framework to integrate the various elements of time in current neighbourhood effects theories. The life course approach emboldens the study of full individual life course biographies over time, taking into consideration multiple parallel life careers (such as education, household, housing, work, and leisure) and their relative importance to individual outcomes. A large advantage of the life course approach to neighbourhood effects is that it does not only allow us to incorporate residential neighbourhoods into individual biographies, but also allows us to study the effects of (and interactions with) other social and spatial contexts on individual outcomes.
Keywords: I30; J60; P46; R23; 330; neighbourhood effects; neighbourhood histories; life course approach; temporal dimension; contextual effects